The effects of Lactobacillus reuteri probiotics combined with azithromycin on peri-implantitis: A randomized placebo-controlled study - Tada, Hiroaki; Masaki, Chihiro; Tsuka, Shintaro; Mukaibo, Taro; Kondo, Yusuke; Hosokawa, Ryuji (Journal of prosthodontic research, 2018)
The aim of this randomized placebo-controlled clinical study was to investigate the effects of a probiotic tablet containing Lactobacillus reuteri in peri-implantitis patients. Subjects comprised 30 patients with mild to moderate peri-implantitis. A baseline clinical examination and microbiological assessment were conducted, followed by an antibiotics treatment (azithromycin, 500mg, once a day for 3 days). Subjects were divided into probiotic and placebo groups. The clinical examination and bacterial sampling were performed 0, 4, 12 and 24 weeks after the intake of probiotics. The clinical examination included probing pocket depth (PPD), bleeding on probing (BOP), the modified plaque index (mPI), and modified bleeding index (mBI). The number of bacteria was assessed using the PCR-invader method. The Wilcoxon rank-sum test and Wilcoxon signed-rank test with Bonferroni corrections were used for data analyses. Although the number of bacteria decreased after the administration of azithromycin in both groups, they increased again thereafter. No significant difference was observed in bacterial numbers between the two groups. Although PPD in the probiotics group was significantly lower at 4 and 24 weeks than at 0 weeks (p<0.05), a significant decrease did not occur in the placebo group. The mBI score at 24 weeks was significantly lower in the probiotics group than in the placebo group (p<0.05). No significant difference was observed in BOP or mPI between the two groups. These results suggested that probiotics prevent inflammation by affecting host responses rather than improving microbial flora in peri-implant sulci in peri-implantitis patients.